Accountors, Accountants, and Standard No. 8 - Choi, Frederick D. S.; Lowe, Howard D.; Worthley, Reginald G. (Journal of International Business Studies, 1978)
This article surveys the reactions of financial executives (accountors) and professional accountants to the Financial Accounting Standards Board's recent pronouncement on foreign currency translation. CPAs were found to be generally supportive of the FASB and the provisions of its controversial standard. Financial executives, in stark contrast, were generally opposed to the major provisions of FASB 8.